Participation of MIR775A in Post-transcriptional Regulation Glycerol-3-phosphatacyltransferases in Corn Leaves under Hypoxia - Fedorin D.N.; Khomutova A.E.; Eprintsev A.T. (Journal of Stress Physiology & Biochemistry)
Oxygen deficiency causes significant changes in plant metabolism related to the coordination of metabolic processes for stress adaptation. MicroRNAs provide regulation of target genes at the post-transcriptional level. The plant cell presents hypoxia-dependent microRNAs, including miR775A, whose quantity increases under these stress conditions. An electrophoretic study of total RNA samples from corn leaves under hypoxia has revealed the presence of two interfering complexes with miR775A at the 12th hour of the experiment. Sequencing and subsequent analysis of the nucleotide sequence of image 2 of the miR775A interfering complex with mRNA from corn leaves have showed a high degree of homology with the N-acyltransferase domain, and corresponded to a fragment of glycerol-3-phosphate acyltransferase mRNA. Inhibition of glycerol-3-phosphate acyltransferase in maize leaf cells under hypoxia can probably provide regulation of cellular fatty acid metabolism under the influence of a stress factor.